2010
DOI: 10.1038/oby.2010.88
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐ to Postoperative Physical Activity Changes in Bariatric Surgery Patients: Self Report vs. Objective Measures

Abstract: Bariatric surgery patients report significant pre- to postoperative increases in physical activity (PA). However, it is unclear whether objective measures would corroborate these changes. The present study compared self-reported and accelerometer-based estimates of changes in moderate-to-vigorous intensity PA (MVPA) from pre- (pre-op) to 6 months postsurgery (post-op). Twenty bariatric surgery (65% laparoscopic-adjustable gastric banding, 35% gastric bypass) patients (46.2 ± 9.8 years, 88% female, pre-op BMI =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
163
3
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 167 publications
(194 citation statements)
references
References 9 publications
18
163
3
10
Order By: Relevance
“…Our results partly cohere with previous studies indicating that candidates for bariatric surgery have low levels of physical activity and that this might have influenced the treatment choice for bariatric surgery [8, 43]. Increased levels of physical activity have been reported after bariatric surgery [44]. Nevertheless, a 6-week preoperative physical activity intervention program improved both physical and mental health as well as self-enjoyment and motivations compared with standard presurgical care in 75 patients (90% women) with mean BMI 45.…”
Section: Discussionsupporting
confidence: 80%
“…Our results partly cohere with previous studies indicating that candidates for bariatric surgery have low levels of physical activity and that this might have influenced the treatment choice for bariatric surgery [8, 43]. Increased levels of physical activity have been reported after bariatric surgery [44]. Nevertheless, a 6-week preoperative physical activity intervention program improved both physical and mental health as well as self-enjoyment and motivations compared with standard presurgical care in 75 patients (90% women) with mean BMI 45.…”
Section: Discussionsupporting
confidence: 80%
“…A number of retrospective cohort studies report a positive association between physical activity and postsurgery weight loss (24)(25)(26)(27)(28). However, these studies are limited by their observational nature, inclusion of only patients who return for follow-up, and subjectively measured physical activity by self-report questionnaires (29).…”
Section: Resultsmentioning
confidence: 99%
“…Increased physical activity after bariatric surgery has been reported to provide additional weight loss (43). However, most of these studies were nonrandomized, retrospective, and observational in nature and measured physical activity by questionnaire and self report (43), methods that may lead to overestimation of exercise participation in obese subjects (44,45), including those who have undergone bariatric surgery (29). Our observations using a semi-supervised exercise intervention are in line with those of Shah et al, who showed that a high-volume exercise prescription following bariatric surgery had no impact on body weight and waist circumference when patients were compared with a control group (20).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of bariatric surgery on PA participation appears to be, at best, trivial [46,47], and therefore, this population is still at risk of health conditions related to inactivity, irrespective of the weight loss and the improvement achieved in obesity-related comorbid conditions. Achieving change in PA behaviour is challenging [13], and some of the perceived barriers identified in this study may be difficult to modify (e.g.…”
Section: Self-presentational Concernsmentioning
confidence: 93%